Syd/JIP3 controls tissue size by regulating Diap1 protein turnover downstream of Yorkie/YAP. - Ahmad, V.; Vadla, G.P.; Chabu, C.Y. (Developmental Biology, 2021)
How organisms control organ size is not fully understood. We found that Syd/JIP3 is required for proper wing size in Drosophila. JIP3 mutations are associated with organ size defects in mammals. The underlying mechanisms are not well understood. We discovered that Syd/JIP3 inhibition results in a downregulation of the inhibitor of apoptosis protein 1 (Diap1) in the Drosophila wing. Correspondingly, Syd/JIP3 deficient tissues exhibit ectopic cell death and yield smaller wings. Syd/JIP3 inhibition generated similar effects in mammalian cells, indicating a conserved mechanism. We found that Yorkie/YAP stimulates Syd/JIP3 in Drosophila and mammalian cells. Notably, Syd/JIP3 is required for the full effect of Yorkie-mediated tissue growth. Thus Syd/JIP3 regulation of Diap1 functions downstream of Yorkie/YAP to control growth. This study provides mechanistic insights into the recent and perplexing link between JIP3 mutations and organ size defects in mammals, including in humans where de novo JIP3 variants are associated with microcephaly.